Pengembangan Data Warehouse dan Aplikasi Investigasi Kecelakaan Kereta Api (Studi Kasus di PT. Kereta Api Indonesia Daerah Operasi IV) - Budiawan, Wiwik; -, Sriyanto; Andika, Wahyu (Performa: Media Ilmiah Teknik Industri, 2014)
Investigation can be a complex task without any supporting system that provide a necessary data or a relevant information (Data Warehouse). Such as investigation of the PT Kereta Api Indonesia (KAI) in analyzing a train accident due to human error that occurs is limited. Analysis conducted by KAI only focuses on individuals who are related and have not been able to analyze in detail because of lack of data. Would require analysis of a train wreck with a systematic method integrated with data warehouse so that recommendations given on target. This study, initially conducted by interview data collection using the Critical Decision Method (CDM) and inferred using the Emergent Themes Analysis (ETA). Then used a systematic method of Human Factors Analysis Classification System Indonesian Railroad (HFACS-IR) to analyze human error especially train accidents that occurred in Indonesia. Later. Before the application is made investigations, required making accident scenarios by using Linking Causal Factor.